Oceanographic Data of the 19th Japanese Antarctic Research Expedition 1977-1978 - Katsuyuki Oda; Masakatsu Nobukuni (Antarctic Record, 1980)
This report presents the results of oceanographic observations, which were carried out by the 19th Japanese Antarctic Research Expedition in 1977-1978.